Perbandingan Pendidikan Islam di Indonesia dan Thailand - Anshori Anshori (STIKes Ibnu Sina Ajibarang, 2023)
This research aims to determine the Islamic education system in Indonesia and Thailand. Islamic education in Indonesia is growing very quickly compared to Southeast Asian countries. The number of madrasas and farmers proves it. Islamic education in Indonesian is one of the mandatory subjects in public schools and universities. In Thailand, 10% is a country where the majority adheres to Buddhism. The Muslim population of the entire population of Thailand. With this amount. The education of minority Muslims in Thailand also has similarities. Islamic Education in Indonesia. There are also Islamic boarding schools in Thailand and madrasas whose education system is not far from that of Indonesia. The only difference is in quantity. Subjects examined in the national exam and the obligation to study Thai there.